Politically Controlled Images: Interpreting Late Roman Silver “Picture Plates" - Milinović, Dino (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić's 70th birthday, 2020)
Late Roman silver plates always had a particular place in art history of the later Roman Empire. Their size and luxury, surpassing similar objects from earlier centuries, and the fact that they represent a major means of imperial and aristocratic self-representation make them an outstanding mirror of the late Roman society, i.e., its elites. The article deals with some of the major ”picture plates” such as the Seuso plate, and some of the more recent finds from Croatia. The distribution of such lavish pieces and the meaning of their iconography is analyzed in the light of specific relations between the emperor and the army, reflecting complex historical circumstances of the 4th century.